Early Starvation Contributes to the Adaptive Capacity of Corythucha marmorata (Uhler), an Emerging Pest in China - Wei Zhou; Wenlong Chen (Biology, 2022)
Food shortages severely reduce the prospects of insect survival in natural settings, including in the case of herbivorous insects. However, the early starvation experience of some insects has positive effects throughout their entire lifespan. It is important to discuss the effects of refeeding and host plants on the capacity of herbivorous insects to adapt to starvation and low temperatures, considering that starvation resistance is expected to show some degree of adaptive phenotypic plasticity. We tested the relationship between host plant, starvation, and the supercooling capacity of the invasive pest Corythucha marmorata. In particular, we highlighted how early starvation affects the refeeding and recovery phases. Among the various range of hosts, the chrysanthemum lace bug has the fastest growth rate on Helianthus annuus, and the strongest supercooling capacity on Symphyotrichum novi-belgii. Especially, starvation for 2 days increases the rates of survival, development, and number of eggs upon refeeding, in comparison to no starvation. A 3-day starvation period in the nymphal stage significantly increased the supercooling capacity of 5th instar nymphs and adults, as observed in our study.